Wisdom and hope in dealing with your non-Muslim family - Seise, Claudia (Azizah) (www.aboutislam.net, 2018)
Our decision to accept Allah into our lives brings a lot of new things, moments, confusions, teachings, and beauty. We see the world with different eyes. We have to give ourselves time to slowly adapt to our new life…